Modification of ISONER Framework as Enterprise Service Bus to Build Consultation Robot Using External Engine - I Made Sukarsa; I Ketut Gede Darma Putra; Nyoman Putra Sastra; Lie Jasa (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2018)
Balinese Calendar, the result of astronomy development, is the foundation for Balinese religious implementation as one of the key elements of tourism industry in Bali. In addition to the printed and electronic versions, an engine that can be used to function as a service for advanced application development is not yet available. Balinese calendar is one of the complementary materials commonly used by Sulinggih in giving consultations about days considered to be the most appropriate to perform ceremonies. Sulinggih is a figure considered to have expertise in Balinese Calendar and its uses. This research will transfer the basic knowledge of Balinese Calendar into an engine on MySQL machine. After the engine undergoes a test, a text-based dialogue model will be designed to form a Sulinggih robot with various natural language algorithms so that it can be accessed through social media messenger services, namely telegram. In order to successfully conduct this research, a phase of system development will be carried out by referring to the System Development Life Cycle model. The process of developing dialog model will involve the use of ISONER framework which will be modified to function as an Enterprise Service Bus(ESB)